Gestión de crédito y cobranza a clientes en la empresa Indumot S.A. de la ciudad de Babahoyo en el año 2021. - Ortiz Chang, Jonathan David (2022)
This study deals with the system of credit management and customer collection in the company INDUMOT S. in the city of Babahoyo in the year 2021, analyzing the parameters that customers must adapt to apply for credit in the company, this being a process with many requirements at the time of wanting to purchase the product. Being very demanding at the moment of granting a credit due to the company's policies, its liquidity or sales may be affected. It is clear that, without making methodologies, the management of collections in the company is not very functional, the credit division must continue and tell the holder of the debt and the co-debtors to have an effective regulatory administration. Thinking that this resource of the credit portfolio is of utmost importance of the company, it is not established a recovery interaction that allows the company to have liquidity to have available a variety of products in the inventory of the store more quickly. If the company were to establish an adequate control or process in the account receivable, with the purpose of ensuring that customers are able to pay their debts on time, the company could have an easier time in paying suppliers and in turn be able to have more products for sale to the public. With the results acquired from the late amounts, they influence the establishment's income, showing that there are no recovery techniques in the company's credit and collection management.